ANALYSING THE SETTLEMENT OF MARITIME SOVEREIGNTY’S DISPUTE CASES BASED ON UNCLOS 1982 - Naranta, Enno Haya Gladya; Muttaqin, Labib (Interdisciplinary Social Studies, 2022)
This paper was written to describe maritime sovereignty disputes under the United Nations Convention on the Law of the Sea 1982 (UNCLOS). UNCLOS' 1982 role was enormous in resolving the South China Sea dispute, Indonesia's Malaysian dispute, and the Natuna islands dispute. The theoretical framework used in this paper to analyze case studies is the international regime and the theory of compliance with maritime dispute resolution. The results of this paper show that the jurisdiction of UNCLOS 1982 offers several paths in dispute resolution and prevents the occurrence of perpetual sea disputes.